KAJIAN VISUAL JAHITAN UTTU PADA TENUN HINGGI DARI KAMBERA, KANATANG, MELOLO DAN RINDI: VISUAL STUDIES OF UTTU STITCHES ON HINGGI WOVEN FROM KAMBERA, KANATANG, MELOLO DAN RINDI - Wahyu Perdana Saputra; Achmad Haldani Destiarmand (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Hinggi is a cultural heritage that come from East Sumba and is one of the woven textiles that can be easily recognized from its distinctive character and ornamentation. In general, hinggi is produced with a warp ikat weaving technique and woven using a backstrap loom. The making hinggi itself requires at least 7 main stages of production, with 42 complicated work steps, including sewing two narrow pieces of fabric to produce a wider sheet of fabric. Besides its major purpose as a jointing stitch, stitches or in the Kambera language referred to as uttu, can be found on a hinggi in a various characteristic and also possess an aesthetic function, However, the presence of uttu stitches often ignored and not noticed because of its tiny size. In fact, the presence of uttu stitches plays an important role in the wholeness of a hinggi fabric and becomes one of the most prominent aspect that highly required in the making of hinggi fabric.